GENDER DIFFERENCES IN THE LINGUISTIC SPHERE: A COMPREHENSIVE ANALYSIS (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the manifestations of gender differences in the linguistic sphere, a topic of growing interest in sociolinguistics and discourse analysis. It delves into how men and women differ in their language use, covering areas such as phonetics, grammar, communication styles, and conversational patterns. The article discusses the role of socialization and cultural norms in shaping these differences and addresses how gendered language influences power dynamics, identity construction, and social interactions. Contemporary studies indicate that while gendered linguistic patterns exist, they are not fixed and are subject to change across cultures and contexts.